Thermomechanical and damage characterisation of short glass fibre reinforced polyamide 6 and impact-modified polyamide 6 composites - Song, P; Trivedi, AR; Chapman, DJ; Graham, A; Hawkins, N; Lukić, B; Rack, A; Siviour, CR (Elsevier, 2024)
Polyamide 6 and its composites are widely used in engineering applications that are exposed to high strain rate deformation. This paper investigates the thermomechanical properties of two polyamide 6 composites, both reinforced with 30 wt% short glass fibres, and one of which additionally contains an impact modifier, to provide an understanding of the mechanical response over a wide range of strain rates and temperatures. Compression experiments were performed at rates between 2 and 3000 s−1, with high speed optical and infrared cameras to aid interpretation of the rate-dependent failure arising from the formation of adiabatic shear bands. Further high strain rate experiments were performed with ultra-fast X-ray phase-contrast imaging to provide in-situ internal damage evaluation. These data will improve the utilization of these composites and aid in development of advanced thermomechanical models.